Legal Transformation for the Achievement of SDGs: Integration of Multidisciplinary Approaches towards 2030 - Aptasari, Ariesca Dwi (RSF Conference Series: Business, Management and Social Sciences, 2024)
This research aims to investigate and analyze the transformation of law in an effort to achieve Sustainable Development Goals (SDGs) through the integration of a multidisciplinary approach. Along with dynamic global changes, the challenges in achieving the SDGs require innovative and adaptive legal strategies. This dissertation focuses on two main problem formulations: first, how the integration of multidisciplinary approaches in legal reform can support the achievement of SDGs; second, how the evaluation and monitoring of legal policies implemented can ensure the achievement of SDGs targets. Through literature review and case analysis, this research reveals that incorporating various disciplines-such as economics, sociology, environmental science, and politics-in the legal policy-making process is key to creating comprehensive and responsive regulations. A multidisciplinary approach not only broadens perspectives in the legal field, but also ensures that the resulting policies are able to address the complexity of sustainable development issues. The research further proposes that an effective evaluation and monitoring system is an essential element to ensure legal policies can be optimally implemented and contribute to the achievement of the SDGs. Suggested measures include the development of relevant performance indicators, stakeholder engagement, and the use of information technology to increase transparency and accountability. With this approach, it is expected that legal reform can adapt to changing conditions and make a positive contribution to the achievement of sustainable development goals, creating a more inclusive and sustainable future for all. This research makes important theoretical and practical contributions to the development of legal policies that are in line with the global agenda for sustainable development.